Sessional Contract Faculty, Unionization, and Academic Freedom - Ross, Stephanie; Savage, Larry; Watson, James (Canadian Journal of Higher Education, 2021)
This article explores the relationship between unionization and academic freedom protections for sessional faculty in Ontario universities. Specifically, we compare university policies and contract provisions with a view to determining whether unionized sessionals hired on a per-course basis have stronger academic freedom protections than their non-union counterparts. We then explore whether particular kinds of bargaining unit structures are more conducive to achieving stronger academic freedom provisions. Finally, we consider whether academic freedom can be exercised effectively by sessionals, whether unionized or not. We conclude that unionization does help to produce stronger academic freedom protections for sessional faculty and that faculty association bargaining unit structures are most likely to help deliver this outcome. We further conclude that academic freedom is difficult to exercise for sessional faculty, regardless of union status, but that unionization offers greater protections for sessionals facing repercussions as a result of asserting their academic freedom.